Active faulting of the Nanhe Fault and relation to the Anninghe Fault zone in the late Quaternary, eastern Tibetan Plateau - Ma, Chao; Liu, Yufa; An, Like; Yang, Xing; Liu, Shao; Zhang, Wei (Frontiers in Earth Science, 2023)
Faults along the boundaries of active tectonic blocks are the main structures that are responsible for major earthquakes in mainland China. Investigating the geometric distribution, rupture behavior, and paleoseismic history of these faults is the prerequisite for constraining geodynamic models and regional seismic hazard analyses. The Nanhe Fault, located at the eastern boundary of the Sichuan–Yunnan Block near Mianning County, has been paid less attention so far due to insufficient historical records of major earthquakes. In this paper, we focused on the Nanhe Fault and conducted satellite imagery interpretation, field investigations, and trench excavations. Our findings indicate that the Nanhe Fault initiates north of Mianning County; the north segment of the fault is connected with the Anninghe Fault; and it extends for about 70 km south-westward and terminates southwest of Ermaga Village. The fault has been faulting in the late Late Pleistocene with a left-lateral strike-slip rate of 2.40–2.56 mm/yr, while in the late Holocene, the left-lateral strike-slip and vertical slip rates are 2.50–2.60 mm/yr and about 0.60 mm/yr, respectively. Three paleoseismic events (5373–4525 BC, AD 1193–1576, and AD 1496–1843) were identified by excavating trenches at the Nanhe Fault. A comparative analysis of paleoseismic events between the Nanhe and the Anninghe fault indicates that both faults may have induced cascade rupture or triggered earthquakes—such related events may have occurred in 1496–1627. Additionally, by comparing the kinematic relationship of the faults at the eastern boundary of the Sichuan–Yunnan Block, we propose that the Nanhe Fault takes part in strain partitioning along the boundary. This interpretation reasonably explains the loss of the sliding rate between the Anninghe and Zemuhe faults, which also supports the GPS inversion results, and the discontinuous deformation model for the eastern margin of the Tibetan Plateau.